Towards a model for a South African clinical psychology - Perkel, Adrian K (PINS-Psychology in Society, 2025)
Apartheid and mental ill-health are inextricably linked in South Africa (Vogelman, 1986). A radical transformation at the structural level remains a prerequisite for appropriate change. In this context neutrality by psychologists is a myth and the choosing of sides an inherent necessity (Dawes, 1985). The clinical psychologist who acknowledges this need and does so is faced with a difficult problematic. How, in attempting to resolve the broad structural issues of societally produced mental ill-health and make him/herself relevant to this task, does the psychologist use his or her skill as a psychologist? In other words, how do we resolve the tension between the clinical psychologist dealing with the individual or system clinically and the need to address the issues of the community or society.